Tinjauan Maslahah Mursalah terhadap Tradisi Kedau Lamban setelah Perkawinan pada Masyarakat Adat Lampung Saibatin di Kabupaten Lampung Barat - Anggara Jaya; Nurnazli Nurnazli; Iskandar Syukur (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the post-wedding Kedau Lamban tradition among the Lampung Saibatin indigenous community in West Lampung Regency using the Maslahah Mursalah perspective of Islamic law. The Kedau Lamban tradition is a customary practice performed after marriage as a means of strengthening family ties and social integration between both families. The research method used was a qualitative study with a normative approach, through data collection through interviews and observations. The results indicate that the Kedau Lamban tradition possesses beneficial values, such as strengthening ties of kinship, maintaining household harmony, and strengthening the social structure of the indigenous community. From the Maslahah Mursalah perspective, this tradition is acceptable as long as it does not conflict with Islamic sharia principles, as it contains tangible benefits for community life. Therefore, the Kedau Lamban tradition can be categorized as a customary practice that aligns with the beneficial values of Islam.